TURNING PROGRAM IMPROVING WRITING SKILLS - Dosanova R.A; Tashkenbay G.T (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Writing skills are the skills you use to write effectively and succinctly. A good writer is someone who can communicate their point to their audience without using too much fluff and in a way that the other person can understand. Writing skills don’t just include the physical act of writing.